Confronting fragmentation function universality with single hadron inclusive production at HERA - Sandoval, Carlos (Array, 2008)
Summary: Predictions for light charged hadron production data in the current fragmentation region of deeply inelastic scattering from the H1 and ZEUS experiments are calculated using perturbative QCD at next-to-leading order, and using fragmentation functions obtained by fitting to similar data from e+e- reactions. Good agreement was obtained with the HERA data from years 1994 to 1997. There is a discrepancy at low Q and small scaled momentum xp, that was reduced by incorporating mass effects of the detected hadron. We also studied the contributions from the different hadron species, as well as from the various quark flavours in the ep reaction by performing quark tagging in the calculation. Comparisons to more recent and precise data show a larger discrepancy due to various neglected effects in our calculation, such as quark masses, soft gluon resummation and higher twist